High overlap in patients diagnosed with hypermobile Ehlers-Danlos syndrome or hypermobile spectrum disorders with fibromyalgia and 40 self-reported symptoms and comorbidities - Fairweather, DeLisa; Bruno, Katelyn A.; Darakjian, Ashley A.; Bruce, Barbara K.; Gehin, Jessica M.; Kotha, Archana; Jain, Angita; Peng, Zhongwei; Hodge, David O.; Rozen, Todd D.; Munipalli, Bala; Rivera, Fernando A.; et al. (Frontiers in Medicine, 2023)
Background Joint pain is a common symptom in patients with hypermobile Ehlers-Danlos Syndrome (hEDS), hypermobility spectrum disorders (HSD) and fibromyalgia. The goal of this study was to determine whether symptoms and comorbidities overlap in patients diagnosed with hEDS/HSD and/or fibromyalgia. Methods We retrospectively examined self-reported data from an EDS Clinic intake questionnaire in patients diagnosed with hEDS/HSD, fibromyalgia, or both vs. controls with an emphasis on joint issues. Results From 733 patients seen at the EDS Clinic, 56.5% (n = 414) were diagnosed with hEDS/HSD and fibromyalgia (Fibro), 23.8% (n = 167) hEDS/HSD, 13.3% (n = 98) fibromyalgia, or 7.4% (n = 54) none of these diagnoses. More patients were diagnosed with HSD (76.6%) than hEDS (23.4%). Patients were primarily White (95%) and female (90%) with a median age in their 30s (controls 36.7 [18.0, 70.0], fibromyalgia 39.7 [18.0, 75.0], hEDS/HSD 35.0 [18.0, 71.0], hEDS/HSD&Fibro 31.0 [18.0, 63.0]). There was high overlap in all 40 symptoms/comorbidities that we examined in patients diagnosed with fibromyalgia only or hEDS/HSD&Fibro, regardless of whether they had hEDS or HSD. Patients that only had hEDS/HSD without fibromyalgia had far fewer symptoms/comorbidities than patients with hEDS/HSD&Fibro. The top self-reported issues in patients that only had fibromyalgia were joint pain, hand pain when writing or typing, brain fog, joint pain keeping from daily activities, allergy/atopy and headache. Five issues that significantly and uniquely characterized patients diagnosed with hEDS/HSD&Fibro were subluxations (dislocations in hEDS patients), joint issues like sprains, the need to stop sports due to injuries, poor wound healing, and migraine. Conclusion The majority of patients seen at the EDS Clinic had a diagnosis of hEDS/HSD plus fibromyalgia that was associated with more severe disease. Our findings indicate that fibromyalgia should be routinely assessed in patients with hEDS/HSD and vis-a-versa to improve patient care.